The Choice of Leg During Pull Test in Parkinson's Disease: Not Mere Chance - Spagnolo, Francesca; Rini, Augusto Maria; Guida, Pietro; Longobardi, Sara; Battista, Petronilla; Passarella, Bruno (Frontiers in Neurology, 2020)
Background: Parkinson's disease (PD) starts asymmetrically and it maintains a certain degree of asymmetry throughout its course. Once functional disability proceeds, people with PD can change their dominant hand due to the increased disease severity. This is particularly true for hand dominance, while no studies have been performed so far exploring the behavioral changes of lower limb utilization in PD according to the lateralized symptom dominance. In the current study, we aim to track the foot preference of participants with PD to respond to the Pull Test. Methods: Forty-one subjects suffering from PD, with a H&Y scale ≤ 2, were recruited. A motor evaluation was performed, including the motor part of the MDS-UPDRS, its axial and lateralized scores (for more and less affected side), two Timed Tests, namely Time to Walk a standard distance (TW, in seconds) and Time Up and Go Test (TUG, in seconds), and the Pull Test. The preferred foot (right or left) involved in the step backward was recorded. Thirty-seven healthy controls underwent a motor assessment which included the Pull Test and the Timed Tests. Both participants with PD and controls were right-handed. To evaluate the relationship between the response to Pull-Test and PD-symptoms, subjects with PD were further divided into two groups: (1) Right more affected side (Right-MAS), and (2) Left more affected side (Left-MAS). Results: Both groups of subjects with PD (Right-MAS and Left-MAS) during the Pull Test shifted significantly their leg use preference toward the opposite side than the more affected side: Right-MAS used preferentially their left leg (71%) and vice versa (p < 0.001). The limb preference shift was especially true for Left-MAS group that almost invariably used their right, dominant leg to respond to the Pull Test (95%). Similar results were obtained comparing people with PD and Controls. Conclusions: This study shows that the limb used to respond to the Pull Test generally predicts the contralateral side of worse PD involvement. As the disease takes place, it prevails over hemispheric dominance: right-handed subjects with left side PD-onset and worse lateralization tend to be hyper-right-dominant, while right-handed subjects with right side PD-onset and worse impairment tend to behave as left-handers. Lateralization of symptoms in PD is still a mysterious phenomenon; more studies are needed to better understand this association and to optimize tailored rehabilitation programs for people with PD.